CLOUD ERP SOFTWARE SUITABILITY ANALYSIS FOR AUTOMOTIVE COMPONENTS SMALL AND MEDIUM INDUSTRY USING ANALYTICAL HIERARCHY PROCESS - Saputra, Mas'ud Adhi; Prabowo, Yunita; Witjaksono, Wahjoe (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2019)
Small and Medium Industry (SMI) is a form of business activity that is not only limited to the business of buying and selling, but there are activities of production process, simple organizational management, and cooperation with other parties. SMI has limited in terms of cost and management of human resources in improving company performance. With the tight competition of the automotive component industry, there needs a strategy to manage SMIs effectively and efficiently. Information Technology (IT) plays a very significant role in actualizing that. Many of automotive component SMIs in Indonesia still run the companies in conventional ways. Though of course, IT is able to make company management better, through the use of Enterprise Resource Planning (ERP) software. The problem statement in this study is the selection of cloud-based ERP software that is suitable for the automotive component SMI. With the cloud-based ERP, automotive component SMIs have a centralized system. To reduce implementation costs, recommended ERP software is open source. In determining the priority of cloud-based ERP software criteria using the Analytical Hierarchy Process (AHP) method. AHP is used to compare three candidates for cloud-based ERP software, namely Odoo, Idempiere and xTuple. The results obtained that Odoo ranks highest compared to two other software candidates. This shows that Odoo is considered to be able to meet the needs of automotive component SMIs for the needs of cloud-based ERP software.